The Mid-Atlantic Bight Dissolved Inorganic Carbon System Observed in the March 1996 DOE Ocean Margins Program (OMP)—A Baseline Study - Huang, Ting-Hsuan; Cai, Wei-Jun; Vlahos, Penny; Wallace, Douglas W. R.; Lewis, Ernie R.; Chen, Chen-Tung Arthur (Frontiers in Marine Science, 2021)
The United States Department of Energy (DOE)’s Ocean Margins Program (OMP) cruise EN279 in March 1996 provides an important baseline for assessing long-term changes in the carbon cycle and biogeochemistry in the Mid-Atlantic Bight (MAB) as climate and anthropogenic changes have been substantial in this region over the past two decades. The distributions of O2, nutrients, and marine inorganic carbon system parameters are influenced by coastal currents, temperature gradients, and biological production and respiration. On the cross-shelf direction, pH decreases seaward, but carbonate saturation state (ΩArag) does not exhibit a clear trend. In contrast, ΩArag increases from north to south, while pH has no clear spatial patterns in the along-shelf direction. In order to distinguish between the effects of physical mixing of various water masses and those of biological activities on the marine inorganic carbon system, we use the potential temperature-salinity diagram to identify water masses, and differences between observations and theoretical mixing concentrations to measure the non-conservative (primarily biological) effects. Our analysis clearly shows the degree to which ocean margin pH and ΩArag are regulated by biological activities in addition to water mass mixing, gas exchange, and temperature. The correlations among anomalies in dissolved inorganic carbon, phosphate, nitrate, and apparent oxygen utilization agree with known biological stoichiometry. Biological uptake is substantial in nearshore waters and in shelf-slope mixing areas. This work provides valuable baseline information to assess the more recent changes in the marine inorganic carbon system and the status of coastal ocean acidification.